2021
DOI: 10.1016/j.heliyon.2021.e07827
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Force and emotionally related imaginations – preliminary results suggest a reduction of the maximal holding capacity as reaction to disgusting food imagination

Abstract: The link between emotions and motor control has been discussed for years. The measurement of the Adaptive Force (AF) provides the possibility to get insights into the adaptive control of the neuromuscular system in reaction to external forces. It was hypothesized that the holding isometric AF is especially vulnerable to disturbing inputs. Here, the behavior of the AF under the influence of positive (tasty) vs. negative (disgusting) food imaginations was investigated. The AF was examined in n = 12 cases using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
143
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(152 citation statements)
references
References 108 publications
(210 reference statements)
8
143
1
Order By: Relevance
“…A priori power analysis (G*Power 3.1.9.7) for group differences (dependent t-test, two-tailed) on the base of the parameter with the lowest effect size of the previous study (unpleasant vs. pleasant imagination; parameter 𝐴𝐹𝑜𝑠𝑐 𝐴𝐹𝑚𝑎𝑥 , dz = 1.390) [11] revealed a necessary sample size of at least n = 9 (α = 0.05, β = 0.95). In the anticipation of possible dropouts and due to an assumed lower effect size because of the improved design with a presumably lower bias, n = 12 participants were measured.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…A priori power analysis (G*Power 3.1.9.7) for group differences (dependent t-test, two-tailed) on the base of the parameter with the lowest effect size of the previous study (unpleasant vs. pleasant imagination; parameter 𝐴𝐹𝑜𝑠𝑐 𝐴𝐹𝑚𝑎𝑥 , dz = 1.390) [11] revealed a necessary sample size of at least n = 9 (α = 0.05, β = 0.95). In the anticipation of possible dropouts and due to an assumed lower effect size because of the improved design with a presumably lower bias, n = 12 participants were measured.…”
Section: Participantsmentioning
confidence: 99%
“…In first pilot studies the AFisomax was found to be significantly reduced in healthy participants perceiving unpleasant vs. pleasant odors [41] as well as by imagining negative vs. positive food experiences [11]. Both, unpleasant odors and negative food imaginations, are related to the emotion 'disgust'.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations